Interface Navigation by Grade-Six Students: A Case Study of Three Multi-Media CD-ROM Products - Large, Andrew; Beheshti, Jamshid; Breuleux, Alain (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Reports research to investigate how two primary school classes retrieved information from CD-ROM multimedia information sources in support of a class project. The students demonstrated confidence in operation the interfaces, but did not find them equally easy or effective. They were able to distinguish between the enjoyment of using an interface and the utility of the CD-ROM as a source. . .